立山におけるチョウノスケソウの個葉特性 中緯度高山帯と寒帯・亜寒帯ツンドラとの比較 - 和田 直也; 中井 祐美; 工藤 岳 (植物地理・分類学会 = The Society for the Study of Phytogeography and Taxonomy, 2003)
We examined leaf traits（i.e. leaf size and shape, leaf dry mass per area（LMA）and leaf nitrogen concentra-tion（LNC））of mountain avens（Dryas octopetala L．）growing at the southernmost extent of its geographical range （mid-latitude alpine）, in Tateyama Mts., central Japan. We then compared leaf traits among a mid-latitude al-pine population（D. octopetala L. var. asiatica（Nakai）Nakai）and high-latitude subarctic and arctic populations （D. octopetala L. var. octopetala）, using data-set of four different populations already reported by Kudo et al．（2001）. A mid-latitude population（Tateyama）had a rotunda-shaped lamina with larger leaf area, while a high-latitude arctic population（Ny-Alesund in Svalbard）showed an elliptical lamina with smaller leaf area. LMA was remarkably lower but LNC was greatly higher in a mid-latitude population than in subarctic（northern Sweden） and high arctic populations. When all data（mean values in each population）were pooled, a negative relationship between LMA and LNC was detected significantly among populations（r= －0.93, P = 0.02）. We discussed these geographical variations in leaf traits from mid-latitude alpine to high arctic tundra in relation to climate vari-ables and water availability.